Measuring Banking Profitability Based on Quality Earning Assets and Net Performing Loan - Trisnawaty, Trisnawaty; Hasmin, Farhana (LPPM STIEM BONGAYA, 2021)
This study aims to determine whether Earning Asset Quality affects Profitability, whether Non-Performing Credit affects Profitability, and to determine whether Earning Asset Quality and Non-Performing Credit have a simultaneous effect on Profitability. Collecting data using secondary data obtained from the financial statements using the cross-sectional technique. The population in this study is the financial statements PT Bank Negara Indonesia Tbk. Branch Makassar Period 2011 – 2019 taken while the sample amounted to 36 pieces. The results of such financial statements have been tested with the classical assumption in the form of normality assumptions, assumptions, and assumptions multicollinearity autokorellasy. Methods of data analysis using multiple linear regression analysis